The secret life of puppets - Nelson, Victoria (Harvard University Press, 2001)
In one of those rare books that allows us to see the world not as we've never seen it before, but as we see it daily without knowing, Victoria Nelson illuminates the deep but hidden attraction the supernatural still holds for a secular mainstream culture that forced the transcendental underground and firmly displaced wonder and awe with the forces of reason, materialism, and science. In a backward look at an era now drawing to a close, The Secret Life of Puppets describes a curious reversal in the roles of art and religion: where art and literature once took their content from religion, we came increasingly to seek religion, covertly, through art and entertainment. In a tour of Western culture that is at once exhilarating and alarming, Nelson shows us the distorted forms in which the spiritual resurfaced in high art but also, strikingly, in the mass culture of puppets, horror-fantasy literature, and cyborgs: from the works of Kleist, Poe, Musil, and Lovecraft to Philip K. Dick and virtual reality simulations. At the end of the millennium, discarding a convention of the demonized grotesque that endured three hundred years, a Demiurgic consciousness shaped in Late Antiquity is emerging anew to re-divinize the human as artists like Lars von Trier and Will Self reinvent Expressionism in forms familiar to our pre-Reformation ancestors. Here as never before, we see how pervasively but unwittingly, consuming art forms of the fantastic, we allow ourselves to believe.